Explorative analyses on spatial differences in the desire for social distance toward people with mental illness in a diverging city - Helmert, Claudia; Speerforck, Sven; Fleischer, Toni; Otten, Danielle; Kasinger, Christoph; Brähler, Elmar; Muehlan, Holger; Altweck, Laura; Hahm, Stefanie; Schmidt, Silke; Reusche, Matthias; Glaesmer, Heide; et al. (Frontiers in Public Health, 2023)
Introduction: Stigma is an individual and societal process, based on attitudes and power, and relates to both, spatial disparities and social distinction. In this study, we examined differences in desire for social distance towards people with mental illness within a city using social and spatial information. Methods: ANOVAs and Scheffé post-hoc tests analyzed varying desires for social distance towards people with mental illness within Leipzig (East Germany). Joint Correspondence Analyses (JCA) explored correspondences between desire for social distance, socio-economic status, age, life orientation, social support, duration of living in Leipzig, and shame towards having a mental illness in five city districts of Leipzig in LIFE study participants (by Leipzig Research Center for Civilization Disease, data collected 2011 - 2014 and 2018 - 2021, n=521). Results: Stigma varied between Leipzig’s districts (F(df=4)=4.52, p=0.001). JCAs showed that higher desired social distance towards people with mental illness corresponded with spatial differences, high levels of pessimism, high shame of being mentally ill, low social support, low socio-economic status, and older age (75.74% and 81.22% explained variances). Conclusion: In terms fo stigma, it matters where people with mental illness live. Results identified target groups that should be addressed by appropriate intervention and prevention strategies for mental health care.